2006
DOI: 10.4103/0973-1482.25858
|View full text |Cite
|
Sign up to set email alerts
|

A typical presentation of acute myeloid leukemia

Abstract: A young man who presented with fever, altered sensorium and sudden onset tachypnea, is described. Arterial blood gas analysis, revealed the presence of severe high anion gap metabolic acidosis, with compensatory respiratory alkalosis and normal oxygen saturation. A detailed neurological, nephrological, biochemical and hematological evaluation, revealed the presence of Acute myeloid leukemia, with lactic acidosis and hyponatremia. There are very few reports of presentation of leukemia as lactic acidosis. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Acute myeloid leukemias (AML) are a heterogeneous group of diseases characterized by infiltration of blood, bone marrow, and other tissues by neoplastic cells of the hematopoietic system (Udayakumar et al, 2006). Approximately two-thirds of adults with AML attain complete remission status after induction therapy; however the remission is often not durable, with about 25% of those whom attained complete remission surviving three or more years.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemias (AML) are a heterogeneous group of diseases characterized by infiltration of blood, bone marrow, and other tissues by neoplastic cells of the hematopoietic system (Udayakumar et al, 2006). Approximately two-thirds of adults with AML attain complete remission status after induction therapy; however the remission is often not durable, with about 25% of those whom attained complete remission surviving three or more years.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review found only five patients with AML associated with type B LA ( 5 , 18 21 ). Among them, lactate clearance impairment was suspected in three patients because of a history of liver cirrhosis ( 5 ), and a possible liver infiltration by leukemia cells as well as severe renal failure were also found ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that chemotherapy administration is the main therapeutic action for fast recovery, with the aim of disrupting lactate production by tumor cells ( 1 ). Regression of hyperlactatemia is the general rule and is a good retrospective argument for WE diagnosis ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acidosis has been reported in many leukemia cases (Warburg effect), some of which are mentioned below [ 3 , 25 - 26 ].…”
Section: Reviewmentioning
confidence: 99%